Teologiczne podstawy monastycznej mistyki nestoriańskiej (syro-orientalnej) w listach Jana z Dalijata - Uciecha, Andrzej (Vox Patrum, 2018)
The article attempts to draw an outline of the mystic theology of the Nestorian monk John of Dalyatha (John Saba, „the Elder”), who lived at the border of what is now Turkey and Iraq at the turn of the 7th and the 8th centuries. His literary output consists of the letters and the homilies and belongs to the „golden age” of the East Syrian Christian literature. In line with the Nestorian Orthodoxy, John Saba denied the perception of the God’s nature, which was identified by him with the transcendent nature of Father. He accepted, however, a contemplation of God’s glory, understood as a radiance and a reflection of the invisible nature. John of Dalyatha was the only mystic who attempted to explain this distinction in the light of ideas of St. Paul (2Cor 3:18 and 4:6). The subject of the current analysis is the idea behind the expressions „remembrance of God” and „the world of changeability”. Unceasing looking at the God, and searching for Him deep into the heart is necessary for the development of mystical sensitivity. The psychological depth of John’s religious programme is striking. In the human soul, the heart is the place of a union with the God, as it was in „the Holy of Holies”. John conveys his spiritual experience, although he is fully conscious of imperfect means through which man can communicate the mysteries of God.